Development of Eco-Stem-Based Worksheets to Enhance Junior High School Students Scientific Creativity - Maretha Dewi Anggraeni; Iwan Wicaksono; Muhd Ibrahim Muhamad Damanhuri (Universitas Lambung Mangkurat, 2026)
Technological developments in the 21st century require students to possess critical and creative thinking skills as well as problem-solving abilities, including scientific creativity. However, science learning in schools still tends to be oriented toward rote memorization and the use of teaching materials that lack innovation, so that students’ scientific creativity has not developed optimally. Previous studies have developed STEM-based worksheets, but few have integrated Eco-STEM approaches specifically to enhance junior high school students’ scientific creativity in science learning. Therefore, this research aims to identify the validity, practicality, and effectiveness of Eco-STEM-based worksheets developed to enhance students’ Scientific Creativity. This research applies the ADDIE development model, which consists of five phases: Analyze, Design, Development, Implement, and Evaluate. The participants in this research were seventh-grade students at State Junior High School No. 2 Kalisat. The results of the research indicate that: (1) the average validity percentage of the worksheets reached 91%, placing them in the “highly valid” category and suitable for use in science education; (2) the average practicality percentage was 89%, indicating that the worksheets are highly practical and easy for students to use; (3) the effectiveness test results showed that Eco-STEM-based worksheets were able to improve students’ scientific creativity skills with an N-gain value of 0.404, which falls into the moderate category; and (4) the average percentage of student responses was 89%, which is classified as “very good,” indicating that the worksheets were effective and received positive feedback from students.